This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x → ∞ lim x e − x = x → ∞ lim e x x
If we plug ∞ in here, we get a ∞ ∞ situation. From here we can go 2 ways:
Method 1: We can argue that e x as grows quicker as x → ∞ than just x . Since e x is in the denominator, we can argue that this limit will tend to 0 (Also, this way of thinking works well with the pun i put for the title :D )
Method 2: We can also use L'Hopital's Rule here and differentiate the top and bottom: x → ∞ lim e x x ⟹ x → ∞ lim d x d ( e x ) d x d ( x ) = x → ∞ lim e x 1 = e ∞ 1 = ∞ 1 = 0